Current and novel therapeutic strategies for optimizing immunotherapy outcomes in advanced non-small cell lung cancer - Martin, Claudio; Enrico, Diego (Frontiers in Oncology, 2022)
During the past decade, immunotherapy has dramatically improved the outcomes of patients with non-small cell lung cancer (NSCLC). The development of specific antibodies against the programmed death (PD1) receptor and its ligands PD-L1 (programmed death ligand-1) have demonstrated substantial efficacy in advanced NSCLC either in the first or second line. However, the success of immune checkpoint inhibitors (ICIs) as monotherapy did not reach all patients and long-responders still represent a small subset of cases. Under these circumstances, different strategies have been and are being tested to optimize clinical outcomes. Here, we reviewed the current evidence and the more promising perspectives of ICI combination approaches, such as the addition of chemotherapy, antiangiogenic agents, other co-inhibitory or co-stimulatory checkpoints, and targeted therapies.